Determinants of chilean exports with a gravitational model 2002-2016 - Fuenzalida - O’Shee, Darcy (2021)
This study aims to determine the variables that may be influencing Chilean exports divided into four groups of goods: manufactures; food, beverages, and tobacco; mining and metals and raw materials of agricultural origin for the period 2002-2016. The study allows us to conclude that Chile's agreements with MERCOSUR, CA and China are not significant in any group of goods; the agreement with members of NAFTA has a negative effect on manufacturing and food, beverages, and tobacco and with EU countries, positive effect only on raw materials of agricultural origin.